1991
DOI: 10.1111/j.1365-2362.1991.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma noradrenaline in cirrhosis: a study of kinetics and temporal relationship to ascites formation

Abstract: The kinetics of plasma noradrenaline (NA) were studied in 14 patients with cirrhosis and ascites and 13 normal subjects. [3H]noradrenaline ([3H] NA) was infused intravenously to steady state and the spillover of NA into plasma and its clearance from plasma calculated. The increase in plasma NA in the cirrhotic patients was due to an increase in NA spillover (14.5 vs 3.9 nmol min-1m-2; P less than 0.001). NA plasma clearance was also increased in the cirrhotic patients (3.5 vs 2.11 min-1m-2; P less than 0.01). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…This could represent the functional correlate for reported downregulation and regression of sympathetic innervation in the mesenteric arterial tree in cirrhosis [10,11]. Besides local SNS downregulation, other potential mechanisms could explain NPY deficiency: unquestionably, systemic NA levels are increased in cirrhosis [3,[6][7][8][9]. This might lead to enhanced a 2 -adrenergic presynaptic inhibition of NPY release [27,28].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This could represent the functional correlate for reported downregulation and regression of sympathetic innervation in the mesenteric arterial tree in cirrhosis [10,11]. Besides local SNS downregulation, other potential mechanisms could explain NPY deficiency: unquestionably, systemic NA levels are increased in cirrhosis [3,[6][7][8][9]. This might lead to enhanced a 2 -adrenergic presynaptic inhibition of NPY release [27,28].…”
Section: Discussionmentioning
confidence: 90%
“…Numerous investigations underline marked SNS activity in cirrhosis [3,[6][7][8][9]. However, recent reports suggest splanchnic sympathetic atrophy in portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the SNS is also present in patients with advanced cirrhosis as evidenced by increased plasma levels of norepinephrine [14]. Measurements of norepinephrine release and spillover in specific vascular beds have shown that the activity of the SNS is increased in many vascular territories, including the kidneys and splanchnic organs [15,16,17]. As occurs with RAAS, inhibition of the SNS in human and experimental cirrhosis results in marked arterial hypotension, suggesting that the SNS is also activated as a homeostatic response to maintain arterial blood pressure [18].…”
Section: Pathophysiology Of Hrsmentioning
confidence: 99%